2016
DOI: 10.1002/hec.3381
|View full text |Cite
|
Sign up to set email alerts
|

Cigarette Taxes, Smoking-and Exercise?

Abstract: This research provides the first in-depth analysis of the effect that increased cigarette taxes have on exercise behavior. Smoking may diminish the ability to exercise; individuals may also use exercise to compensate for the harmful health effects of smoking or to avoid gaining weight if they cut back. Our conceptual model highlights these and several other avenues for effect and reveals that the predicted effect of cigarette costs on exercise behavior is theoretically ambiguous. To investigate the relationshi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 42 publications
0
1
0
Order By: Relevance
“…Studies in young and older adults have shown lower physical endurance and decreased exercise frequency in smokers than in non-smokers. [46][47][48] Over time, physical inactivity and chronic smoking often lead to all-cause mortality and comorbidities such as type-2 diabetes, cardiovascular disease, stroke, and cancer or chronic lung disease. 49,50 Despite regular physical activity reducing up to 30% of the risk of all-cause mortality in both smokers and non-smokers, the more significant benefits are generally observed when exercising at goal levels and quitting smoking.…”
Section: The Behavioral Relevance Of Crf Cardiovascular and Brain Ris...mentioning
confidence: 99%
“…Studies in young and older adults have shown lower physical endurance and decreased exercise frequency in smokers than in non-smokers. [46][47][48] Over time, physical inactivity and chronic smoking often lead to all-cause mortality and comorbidities such as type-2 diabetes, cardiovascular disease, stroke, and cancer or chronic lung disease. 49,50 Despite regular physical activity reducing up to 30% of the risk of all-cause mortality in both smokers and non-smokers, the more significant benefits are generally observed when exercising at goal levels and quitting smoking.…”
Section: The Behavioral Relevance Of Crf Cardiovascular and Brain Ris...mentioning
confidence: 99%